Problems of machine translation of specialized discourse. The case of concepts in medical biology - KHARMOUM , Abdelaâli; ATMANI , Mohammed (Revue Internationale du Chercheur, 2024)
Translation is a linguistic operation that serves to transmit a message from one language into another as faithfully as possible. It is a human activity that is carried out with the help of linguistic and extralinguistic cues. The translation is in fact much more than the knowledge of two languages. It also requires knowledge of the culture, traditions, implicit and explicit of a language and, not least, knowledge of one’s native language and the ways of saying things in that language. A successful translation is one that is comprehensible and coherent in restoring the meaning of the text and the meaning of the author. Our paper is effectively oriented towards the operation of machine translation for the treatment of medical texts, in particular concepts in medical biology by raising its qualities and its failures. Ultimately, in this paper, our aim is to demonstrate the extent to which machine translation can be used as an effective tool, and what steps are necessary to guarantee high-quality translation, highlighting the irreplaceable role of the human translator in this process.